Świadomość mężczyzn - studentów kierunków medycznych z różnych krajów na temat samobadania piersi przez kobiety i jego znaczenia w profilaktyce nowotworów - Pietraszek, Agata; Charzyńska-Gula, Marianna; Łuczyk, Marta; Stanisławek, Andrzej; Kozioł, Anna; Kocka, Katarzyna; Kocki, Tomasz (Journal of Education, Health and Sport, 2015)
Pietraszek Agata, Charzyńska-Gula Marianna, Łuczyk Marta, Stanisławek Andrzej, Kozioł Anna, Kocka Katarzyna, Kocki Tomasz. Świadomość mężczyzn - studentów kierunków medycznych z różnych krajów na temat samobadania piersi przez kobiety i jego znaczenia w profilaktyce nowotworów = The awareness of male students of medical sciences from various countries related to breast self-examination among women and its importance for cancer prophylactics. Journal of Education, Health and Sport. 2015;5(9):493-504. ISSN 2391-8306. DOI10.5281/zenodo.31299 http://dx.doi.org/10.5281/zenodo.31299 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A493-504 https://pbn.nauka.gov.pl/works/631300 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 22.09.2015. Świadomość mężczyzn - studentów kierunków medycznych z różnych krajów na temat samobadania piersi przez kobiety i jego znaczenia w profilaktyce nowotworów The awareness of male students of medical sciences from various countries related to breast self-examination among women and its importance for cancer prophylactics Agata Pietraszek 1, Marianna Charzyńska-Gula2, Marta Łuczyk1, Andrzej Stanisławek1, Anna Kozioł3, Katarzyna Kocka1, Tomasz Kocki4 1. Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Polska 2. Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu, Polska 3. Samodzielny Publiczny Szpital Kliniczny nr 4 w Lublinie, Polska 4. Katedra i Zakład Farmakologii Doświadczalnej i Klinicznej, II Wydział Lekarski z Oddziałem Anglojęzycznym, Uniwersytet Medyczny w Lublinie, Polska Streszczenie Cel pracy: Poznanie świadomości mężczyzn różnych narodowości studiujących nauki medyczne na temat samobadania piersi jako metody wczesnego wykrywania raka piersi oraz opisanie podstawowych uwarunkowań przejawianych przekonań i poglądów. Materiał i metody: Badania przeprowadzono wśród 208 studentów medycyny z Polski oraz krajów obcojęzycznych. Wszyscy respondenci studiowali na lubelskiej uczelni medycznej. Narzędziem badawczym zastosowanym w pracy był autorski kwestionariusz ankiety stworzony dla potrzeb niniejszego badania. Wyniki: Większość respondentów nie posiadało wiedzy o tym, czy kobiety z ich otoczenia wykonują samobadanie piersi. Była to najczęstsza odpowiedz zarówno wśród mężczyzn z Polski jak i z zagranicy. Niemal ¼ respondentów z Polski i jedynie 16% studentów z zagranicy było pewnych, że kobiety z ich otoczenia badają swoje piersi. Nawet 72% ogółu respondentów twierdziło zdecydowanie, że samobadanie jest ważnym aspektem profilaktyki piersi. Odpowiedziało tak 84,44% respondentów z Polski i 62,71% respondentów z zagranicy. Wnioski: Mężczyźni z Polski istotnie częściej doceniali ważność samobadania w profilaktyce nowotworu piersi aniżeli ich zagraniczni koledzy. Dodatkowo to większość Polaków wskazywała prawidłowe odpowiedzi, w zakresie zasad samobadania piersi, aniżeli mężczyźni z innych krajów. Należy podjąć działania zwiększające świadomość oraz wiedzę mężczyzn na temat wczesnej profilaktyki nowotworu piersi wśród kobiet. Słowa kluczowe: wiedza o zdrowiu, postawy, profilaktyka, świadomość; zdrowie kobiety, samobadanie piersi. Abstract Objective: To find out about the awareness among men of various nationalities studying medical sciences on breast self-examination as a method of the early detection of breast cancer and to describe the major determinants of the identified views and beliefs. Material and methods: The survey was carried out among 208 students of medicine from Poland and other countries. All the respondents studied at the Medical University of Lublin. A questionnaire prepared by the authors for the purposes of the study constituted the research instrument. Results: Most respondents did not have any knowledge on whether women in their nearest environment practiced breast self-examination. This was true both about men from Poland and from abroad. Almost one fourth of the respondents from Poland and only 16% of students from abroad were sure that women in their environment performed breast self-examination. As many as 72% of the surveyed were of the opinion that self-examination definitely is an important aspect of breast cancer prophylactics. The statement was confirmed by 84.44% of respondents from Poland and 62.71% of those from abroad. Conclusions: Men from Poland significantly more often recognised the significance of self-examination in breast cancer prophylactics than those from other countries. Furthermore, more Poles than men from other countries selected the correct answers to questions concerning breast self-examination. Therefore, measures should be taken to increase the awareness and knowledge of men about early breast cancer prophylactics among women. Key words: health knowledge, attitudes, practice, awareness, women’s health, breast self-examination.